The Effect of Analytic Cognitive Style on Credulity - Ballová Mikušková, Eva; Čavojová, Vladimíra (Frontiers in Psychology, 2020)
The main aim of this paper was to distinguish between the effect of analytic thinking and relying on cues about the suspicious source of information (astrology). In two experiments (N = 965) analytic thinking was induced and manipulated with the source of fake profile (astrological reading vs. psychological testing) and participants’ prior paranormal beliefs, anomalous explanation, cognitive reflection, and negative emotionality were measured. Although analytic thinking was proved to be hard to induce experimentally, the results showed that analytic thinking predicts credulity and belief in the paranormal was linked with experiencing more anomalous experiences and more paranormal explanations. The more people were able to think analytically, the less credulous they were as reflected in the lower acceptance of fake profile as accurate.